The Factor-Price Frontier, Duality and Joint Production - Burmeister, E.; Kuga, K. (Review of Economic Studies, 1970)
Edwin Burmeister, Kiyoshi Kuga; The Factor-Price Frontier, Duality and Joint Production1, The Review of Economic Studies, Volume 37, Issue 1, 1 January 1970, Pa